Analisis Pengaruh Motivasi Terhadap Kinerja Karyawan Bank - Vigo Hariyanto; Theofilus Samalelo; Catharina Aprilia Hellyani (Jurnal Kajian dan Penelitian Umum, 2023)
The purpose of this research is to analyze the effect of work motivation on the performance of employees at the bank. Motivation is defined as a condition that influences the emergence, direction, and behavior related to performance. This motivation arises from individual desires, drives, needs, hopes, goals, and objectives. When a person has a need, there is an urge to work. Motivation is the driving force for achievement and the basis for enthusiasm in achieving maximum productivity. Motivation influences how individuals apply their potential productively to achieve company goals and targets. The conclusion of this study is that by providing good motivation to employees can increase their morale, and the main factor in achieving company goals is to build good relationships between companies and employees..